“I feel like sometimes it might be too late”: An Interpretative Phenomenological Analysis of Care Experienced Individuals’ Preparation for Adulthood. - Stone, Taylor (2024)
Care Experienced Individuals (CEI) are found to experience disadvantage in adulthood compared to the general population across a range of domains, including health, education, and employment. Research indicates that CEI often experience an accelerated transition to adulthood, characterised by abrupt endings to support, which has been defined as the Care Cliff. Interpretation of research from an ecological perspective illuminates the influence of variables which compound CEIs’ transition to adulthood and highlights the importance of their meaningful participation in decision-making. Despite this, CEIs’ views have been found to be sought tokenistically, indicating a role for Educational Psychologists (EP) for promoting CEIs’ voice in line with the Special Educational Needs and Disabilities Code of Practice 2014 (Department for Education & Department of Health, 2015). A systematic literature review found there was a lack of consideration given to CEIs’ experiences of preparing for adulthood, particularly that which pertains to EP practice. This research aims to address this gap, informed by the Lundy Model of Participation (2007) to explore how CEIs’ voice can influence EP practice.